Identification of Waste Using Waste Assessment Model Method in the Application of Lean Manufacturing at PT. X - Fasha Husna Wicitra; Rus Indiyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
PT X is a company that produces animal feed for poultry such as chickens, ducks, quails, and pigs. The animal feed products offered are in accordance with the nutritional needs of each growth period. The form of animal feed produced by PT X can be in the form of concentrates, mash, pellets or crumble. The challenge faced by PT X is that with the variety of products produced and the relatively large scale of production, the products produced often experience defects, so the products must be held in the warehouse for further processing. Forms of defects detected include abnormal texture, high moisture, and mixing. In addition, defects due to torn sacks also cause non -value-added activities because the products must be repackaged, resulting in delays in the delivery of orders for these products. The problem will be analyzed using the waste assessment model method to find critical waste, then a fishbone diagram is used to find the root of the problem and improvement proposals will be made using the 5W1H method. from the results of the calculation using the WAM method, the final results of the calculation using the Waste Assessment Model (WAM) method show that the highest waste in the animal feed production process is waste defects with a percentage value of 29.20%, waste inventory with a percentage of 19.63% and waste motion with a percentage of 13.20%. Then, improvement proposals will be given, including increasing operator training and evaluating the production process, implementing a digital-based monitoring system such as ERP / WMS for real-time stock visibility, adding conveyors or handlifts in the loading area to minimize manual load lifting movements to make it more effective. From the proposed improvements given, it can reduce the lead time by about 373.33 seconds or 6 minutes and 13 seconds.